Quantum Groups - Dobrev, Vladimir K. (De Gruyter Studies in Mathematical Physics, 2017)
With applications in quantum field theory, general relativity and elementary particle physics, this two-volume work studies the invariance of differential operators under Lie algebras, quantum groups and superalgebras. This second volume covers quantum groups and quantum algebras, supersymmetry and Virasoro algebras.